2006
DOI: 10.1111/j.1574-6968.2006.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment ofStreptococcus mutanswith antisense oligodeoxyribonucleotides togtfBmRNA inhibits GtfB expression and function

Abstract: We examined the effects of phosphorothioate-modified antisense oligodeoxyribonucleotides (PS-ODN) targeted to mRNA transcribed from gtfB, which encodes synthesis of water-insoluble glucans in Streptococcus mutans. Treatment of S. mutans with 10 muM antisense PS-ODNs inhibited gtfB mRNA transcription, GtfB expression and water-insoluble glucan synthesis. The architecture of biofilms formed by antisense PS-ODNs-treated S. mutans showed reduced biomass, more dispersed distribution with enlarged interspaces and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Our studies revealed that 2A4 altered expression of six biofilm-associated genes in planktonic cells of S. mutans. These genes included the adherence-associated gene pac (24), glucosyltransferase gene gtfB (10,42), glucan binding protein-encoding gene gbpB (36), acid-producing gene ftf (16,38), relA, and regulatory gene comDE. They have been linked to different steps of biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies revealed that 2A4 altered expression of six biofilm-associated genes in planktonic cells of S. mutans. These genes included the adherence-associated gene pac (24), glucosyltransferase gene gtfB (10,42), glucan binding protein-encoding gene gbpB (36), acid-producing gene ftf (16,38), relA, and regulatory gene comDE. They have been linked to different steps of biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of results reported by Guo et al (7), we selected 10 μM as the final concentration of PS-ODNs for treatment of streptococci, and also applied the similar transfection reagent (TurboFect™) consisting of a cationic polymer in order to facilitate penetration of the PS-ODNs to the bacterial cells. The cationic polymer forms complexes with PS-ODNs via electrostatic interaction between negatively charged oligonucleotide molecules and positively charged reagent molecules (7,15). Since such complexes maintain the positive charge, therefore they can bind to the negatively charged bacterial cell wall, and then can be taken up by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The currently available antisense technology provides the novel approach that can be applied for blocking the production of glucan polymers in S. mutans bacteria (7). It is based on the use of chemically modified single-stranded nucleic acid molecules (usually 20 nt in length), which can selectively hybridize to their target complementary mRNA through Watson-Crick base pairing, consequently leading to degradation of the bound mRNA by RNase H endonuclease, steric hindrance of ribosomal activity, inhibition of mRNA splicing or destabilization of pre-mRNA (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validated essential genes among different bacterial species include fbpA/ fbpB/fbpC (Harth & et al, 2002(Harth & et al, , 2007 and glnA1 (Harth & et al, 2000) in Mycobacterium tuberculosis, gyrA/ompA in Klebsiella pneumonia (Kurupati & et al, 2007), inhA in Mycobacterium smegmatis (Kulyte & et al, 2005), oxyR/ahpC in Mycobacterium avium (Shimizu & et al, 2003), NPT/EhErd2 in Entamoeba histolytica (Stock & et al, 2000(Stock & et al, , 2001, gtfB in Streptococcus mutans (Guo & et al, 2006), fmhB/ gyrA/hmrB (Nekhotiaeva & et al, 2004a) and fabI (Ji & et al, 2004) in Staphylococcus aureus, 23S rRNA (Xue-Wen & et al, 2007), 16S rRNA plus lacZ/bla (Good & Nielsen, 1998), and RNAse P (Gruegelsiepe & et al, 2006) in Escherichia coli, and acpP in Burkholderia cepacia (Greenberg & et al, 2010), Escherichia coli (Deere & et al, 2005b;Geller & et al, 2003aGeller & et al, , 2003bGeller & et al, , 2005Mellbye & et al, 2009Mellbye & et al, , 2010Tan & et al, 2005;Tilley & et al, 2007) as well as Salmonella enterica serovar Typhimurium (Mitev & et al, 2009;Tilley & et al, 2006). Mellbye et al, First proof-of-principle evidence was given by White et al in 1997 for successful increasing the bactericidal activity of norfloxacin by antisense inhibiting the marRAB operon in Escherichia coli (White & et al, 1997).…”
Section: Validated Targets In Bacteria 22221 Targeting Essential mentioning
confidence: 99%